THE ROLE OF DIGITAL TECHNOLOGY IN SUPPORTING TOURISM INDUSTRY POST COVID-19 (CASE STUDY YOGYAKARTA TOURISM DEVELOPMENT - Dewi, IC; Isdarmanto, I; Makiya, Kiki Rizki (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2022)
The empirical phenomenon of the COVID-19 Virus has caused hardly disaster for all people around the world. Changes from various aspects of the world of the tourism industry, education, and socio-cultural that must run and carry out an innovation strategy in response to the demands of all millennials needs in the pandemic post-COVID-19. The tourism industry has stopped operating for supported government policies to prevent the spread of the COVID-19 virus. This research uses qualitative research by observation and searching information, which gives more flexibility in translating information more worthy and hoping the data are relevant to the research objectives and applied sustainably. The support for the development of digital information technology has to be improved fast. In fact, it helps to provide many opportunities for every individual in society to still be able to carry out business activities and innovations online, so as to cover the needs for their survival. Thus, this research is able to get a strategic solution to the impact of post-pandemic COVID-19 on sustainable tourism education development.